Comparing action disorganization syndrome and dual-task load on normal performance in everyday action tasks. - Morady, K; Humphreys, G (2008)
The term 'action disorganization syndrome' has been used to describe patients with selective impairments in carrying out multi-step everyday tasks, which are not linked to motor deficits. We used a range of everyday life tasks to examine the effects on a patient with ADS of having related distractors present during task performance. The presence of related distractors increased omission errors in the patient. In a second experiment we assessed whether we could mimic this pattern of deficit when normal participants carried out the everyday tasks and a secondary task was imposed to place demands on executive processes. Secondary task load produced a general increase in errors in the controls and reduced the number of self-correcting responses, but there were no proportional increases in omission errors. Control participants and patients with ADS may suffer from demands on different processes involved in the performance of everyday actions. We discuss the implications for understanding everyday actions.